Understanding advanced physical inorganic chemistry : the learner's approach - Tan, Jeanne; Chan, Kim Seng. (Singapore : WS Education, 2011)
Written for students taking either the University of Cambridge A-level examinations or the International Baccalaureate examinations, this textbook covers essential topics under both stipulated chemistry syllabi. It is written in such a way as to guide the reader through the understanding and applications of essential chemical concepts by introducing a discourse feature-the asking and answering of questions-that stimulates coherent thinking and hence, elucidates ideas. Based on the Socratic Method, questions are implanted throughout the book to help facilitate the reader's development in forming logical conclusions of concepts. The book helps students to master fundamental chemical concepts in a simple way. --Back Cover
Topics are explored through an explanatory and inquiry-based approach. They are interrelated and easy to understand, with succinct explanations/examples being included, especially on areas that students frequently find difficult. Topics address the whys and hows behind key concepts to be mastered, so that the concepts are made understandable and intuitive for students. The focus is on conceptual learning so as to equip students with knowledge for critical learning and problem solving. --Back Cover
Existing A-level textbooks and guidebooks generally introduce concepts in a matter-of-fact manner. This book adds a unique pedagogical edge which few can rival. Through their many years of teaching experiences, the authors have acquired a sound awareness of common students' misconceptions which are relayed through the questions and thus help to reinforce concepts learnt. --Back Cover.
Includes index.
Keywords: Physical inorganic chemistry